Ascorbic Acid and Esketamine for Mental Disorders in Women with Miscarriage: A Randomized Controlled Double-Blind Trial Protocol - Ke Z; Zhang Y; Cai B; Luo J; Ma Y; Chen Q; Deng L (Neuropsychiatric Disease and Treatment)
Zhaojuan Ke,1 Ying Zhang,1 Binyang Cai,1 Jie Luo,1 Yao Ma,2 Qibin Chen,1 Linya Deng1 1Department of Anesthesiology, The First Affiliated Hospital of Chongqing Medical University, Chongqing, 400016, People’s Republic of China; 2Department of Geriatrics and National Clinical Research Center for Geriatrics, West China Hospital, Sichuan University, Chengdu, Sichuan Province, 610041, People’s Republic of ChinaCorrespondence: Jie Luo, Department of Anesthesiology, The First Affiliated Hospital of Chongqing Medical University, No. 1 Youyi Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Tel +86-023-89011069, Email jieluo@cqmu.edu.cnPurpose: Pregnancy leads to vulnerabilities and susceptibilities to mental disorders. Miscarriage, as an adverse pregnancy outcome, and following curettage for treatment, add the risks of further psychiatric disorders, including depression, anxiety, insomnia, etc., and current approaches to prevention are unsatisfactory. Ketamine and its S-enantiomer esketamine can prevent postpartum depression, and esketamine even treats depressive symptoms after miscarriage curettage, but their side effects bring limitations. Ascorbic acid (AA, Vitamin C) can modulate mood and enhance ketamine’s antidepressant efficacy synergistically, reducing its dosages and adverse effects potentially. The purpose of this study is to clarify the beneficial modification of AA on esketamine for preventing depression and other mental disorders in patients with miscarriage after painless curettage, as well as the interaction between AA and esketamine.Patients and Methods: This study is a 2× 2 factorial, double-blinded, randomized, controlled trial that will recruit women with miscarriage undergoing painless curettage. A total of 424 participants will be recruited and randomly 1:1:1:1 allocated to the following four groups (106 in each): Group A0K0 (normal saline and normal saline), Group A0K1 (normal saline and esketamine), Group A1K0 (AA and normal saline), and Group A1K1 (AA and esketamine). The primary outcome is the incidence of depression on postoperative day 7, assessed with the Edinburgh Postnatal Depression Scale (EPDS). The secondary outcomes include the EPDS score, assessments of anxiety, sleep, and pain, adverse events, perianesthetic data and patient satisfaction.Discussion: This study provides the clinical trial-based evidence of the effects of AA alone or in combination/interacting with the emerging rapid-acting antidepressant esketamine on depression and other mental disorders in patients with miscarriage undergoing painless curettage. Our data are expected to suggest AA’s potential application for optimizing strategies of promoting post-miscarriage mental health, and its possible adjunctive improvement of (es)ketamine’s usage as antidepressants. One major limitation is that this study is a single-center study, and the results might be biased due to regional factors.Keywords: ketamine, vitamin C, depression, anxiety, sleep disorders, pain